Investigation on PVDF Based Solid Polymer Electrolytes for Rechargeable Lithium Batteries - N.S. Mohamed; S.A. Hashim Ali; A.K. Arof (Institut Teknologi Bandung, 2004)
Solid polymer electrolytes consisting of PVDF and LiCF3SO3 plasticized with different amounts of EC plasticizer were prepared by solution casting method. The addition of plasticizer significantly improved the ionic conductivity. The temperature dependence of ionic conductivity of the plasticized PVDF film follows VTF empirical form, i.e the migration of ions depends mainly on the segmental movements of the polymer chain in the amorphous region. The characteristics of the cell employing the highest conducting system are also presented in this paper.